2015
DOI: 10.5539/elt.v8n3p97
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Concepts of Natural Sciences to Foreigners through Content-Based Instruction: The Adjunct Model

Abstract: This study investigates three models of content-based instruction in teaching concepts and terms of natural sciences in order to increase the efficiency of teaching these kinds of concepts in realization and to prove that the content-based instruction is a teaching strategy that helps students understand concepts of natural sciences. Content-based education is considered effective not only in acquiring the skills of language, but also grasping and mastering the content knowledge of academic subjects that are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…According to [33], the goal of these three models focuses on teaching course material to students on a regular interval, to achieve content knowledge and language proficiency. In this regard, the theme-based model of CBI is widely utilized in teaching L2 learners with lower proficiency, in content areas such as science and humanity courses, by selecting topics that are of interest to the students [33].…”
Section: Cbi and Academic Achievementmentioning
confidence: 99%
See 2 more Smart Citations
“…According to [33], the goal of these three models focuses on teaching course material to students on a regular interval, to achieve content knowledge and language proficiency. In this regard, the theme-based model of CBI is widely utilized in teaching L2 learners with lower proficiency, in content areas such as science and humanity courses, by selecting topics that are of interest to the students [33].…”
Section: Cbi and Academic Achievementmentioning
confidence: 99%
“…According to [33], the goal of these three models focuses on teaching course material to students on a regular interval, to achieve content knowledge and language proficiency. In this regard, the theme-based model of CBI is widely utilized in teaching L2 learners with lower proficiency, in content areas such as science and humanity courses, by selecting topics that are of interest to the students [33]. This method is often combined with the sheltered and adjunct models of CBI; additionally, [33] explains that universities often employ a blended approach that usually incorporates the adjunct model, because studies have shown the intervention produces increased academic achievement from the students involved in the program.…”
Section: Cbi and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Theme-based CBI has been widely accepted and is the most popular CBI teaching model in foreign business language learning (Satilmis, Yakup, Selim, & Aybarsha, 2015). Unlike the traditional business English classes, where the topics are selected from a textbook, theme-based courses highlights the student-centered teaching model (Satilmis et al, 2015); the course is formed by selecting interesting topics which are concerned with students' needs, requirements and interests, especially about a wide range of social heated issues.…”
Section: Theme-based Language Instruction Modelmentioning
confidence: 99%
“…Unlike the traditional business English classes, where the topics are selected from a textbook, theme-based courses highlights the student-centered teaching model (Satilmis et al, 2015); the course is formed by selecting interesting topics which are concerned with students' needs, requirements and interests, especially about a wide range of social heated issues. More importantly, it can allow the implementation of various kinds of language tasks and the choice of some case studies around the subject.…”
Section: Theme-based Language Instruction Modelmentioning
confidence: 99%